Cortical Distance but Not Physical Distance Modulates Attentional Rhythms - Chen, Airui; Zu, Guangyao; Dong, Bo; Zhang, Ming (Frontiers in Psychology, 2020)
It has been well documented that the spotlight of attention is intrinsically rhythmic and oscillates by discretely sampling either single or multiple objects. However, the neural site of attentional rhythms remains poorly understood. In the present study, we aimed to investigate the roles played by visual cortical areas which left and right visual spaces are represented far from each other in attentional rhythms. Considering the topography of visual cortical areas, we modulated the cortical distances of two gratings while fixing the corresponding retinal distance by setting the gratings on the same side (cortically near, Exp. 1) or on different sides of the vertical meridian (cortically far, Exp. 2). The cue-target stimulus onset asynchrony (SOA) varied from 0.1 s to 1.08 s in 20 ms increments, allowing fluctuations below 50 Hz to be examined. The results showed that when the two stimuli were on opposite sides of the vertical meridian, attentional rhythms were observed at theta and alpha frequencies, consistent with the results reported in previous studies. However, when the two stimuli were located on the same side of the vertical meridian, attentional rhythms were not observed. This study indicates that attentional rhythms could be modulated by cortical distance not by physical distance.